PEMBATALAN BERBAGAI PERATURAN DAERAH YANG MEMPENGARUHI PELAYANAN PUBLIK DUNIA BISNIS DAN INVESTASI TINJAUAN EKONOMI DAN BISNIS - Octovianus Nawa Pau (Journal of Management Small and Medium Enterprises (SMEs), 2016)
This article discusses about the cancellation of various local regulations by the Central Governmentin Jakarta which is inhibited the rate of investment in local region. It is contrary to higher level ofregulations and is contrary to the public interest. According to Act (UU) No. 23 year 2014 aboutLocal Government, the regional policies (Perda or Perkada) can be cancelled by the CentralGovernment (Minister of Home Affairs) totally and/or partially. The Ministry of Home Affairsissued instruction of Minister of Home Affairs No. 582/476/SJ on February 16th, 2016 aboutrevocation/changing of Local Government Regulations (Perda) and announced the cancellation ofvarious local regulations including Perda in Regencies, City and East Nusa Tenggara Province.The Central Government had cancelled 3,143 of Perda including 45 of Perda in City and Regenciesin East Nusa Tenggara. The used method for discussion in this article is data compilation studyfrom another articles written by the author previously. Investigation showed that the RegionAutonomy Policies was suspected increasing the transaction cost in investing process both foreigninvestment and domestic investment. Investors who applied the licensing faced many charges whichare relatively greater than before decentralized authority. In addition, the services by investmentorganization authority in the region charged uncertainty cost and time of completion of the licensingprocess. Therefore, the Central Government evaluated the various local regulations which hamperinvestment in the local area. Cancellation of various Perda by the Central Government impacted oneconomic and business sectors in reducing bureaucracy regulatory barriers and the number ofcharges which burden the business sector, thus it will encourage investment in the region. However,the cancellation has reduced local government’s authority for gaining financial from Perda thatwill reduce the regional revenuesKeywords: Local regulations,busines sector, public services, investment